Leukemic optic nerve infiltration as the first symptom of neuroleukemia - E. E. Grishina; A. A. Ryabtseva; O. M. Andryukhina; A. O. Mamontov (Российский офтальмологический журнал)
Extramedullary leukemic foci in acute leukemia attract special attention. They reflect the diversity of clinical manifestations of the disease, affect the severity of the patient’s condition and may influence the choice of treatment strategy. Purpose: to present a rare clinical case of leukemic optical neuropathy in a patient with acute lymphoblast leukemia. Results. Decreased visual acuity of both eyes related to the involvement of the optic nerve was one of the main complaints of the female patient during the onset of the diseases. A loose greyish tumor with blurred contours was identified on the optic nerve disc, with a large number of hemorrhages in various layers of the peripapillary retina. During ophthalmoscopy, the central vessels in the optic disc funnel could not be distinctly differentiated. Brain and orbit MRI showed intraocular masses in the area of the projection of the optic nerve disc and a lesion in the left frontal lobe. There were no signs of high intracranial pressure. After the first chemotherapy course for acute leukemia, visual acuity of both eyes increased, along with a substantial regression of tumor infiltration of the optic disc, which made it possible to visualize the border of the optic disc and the central retinal vessels. Follow-up images showed a full regression of the mass in both eyeballs. The left frontal lesion, whose origin was unclear, remained unchanged. Conclusion. An isolated lesion of the optic nerve could be a potential first sign of neuroleukemia, so it should be on the list for differential diagnosis of optic nerve disorders. First of all, leukemic optic neuropathy should be differentiated from optic nerve edema. Early diagnosis of neuroleukemia and adequate anti-tumor treatment allow for significant improvement of visual acuity and hence, for better quality of life of patients with leukemia // Russian Ophthalmological Journal, 2016; 4: 64-8. doi: 10.21516/2072-0076-2016-9-4-64-68. .